2018
DOI: 10.1016/j.cub.2018.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Natural Infection of C. elegans by an Oomycete Reveals a New Pathogen-Specific Immune Response

Abstract: In its natural habitat, the nematode Caenorhabditis elegans encounters a plethora of other organisms, including many that are pathogenic [1, 2]. The study of interactions between C. elegans and various pathogens has contributed to characterizing key mechanisms of innate immunity [2-4]. However, how C. elegans recognizes different pathogens to mount pathogen-specific immune responses remains still largely unknown [3, 5-8]. Expanding the range of known C. elegans-infecting pathogens and characterizing novel path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(97 citation statements)
references
References 55 publications
0
97
0
Order By: Relevance
“…Notably these genes do not include the well-characterized neuropeptide nlp defense genes, although they do include many of the pals genes. A more recently described natural pathogen of C. elegans is Myzocytiopsis humicola , which is an oomycete that also infects through the epidermis and causes a lethal infection [19]. Here as well, pals-22/25 regulate a significant number of genes in common with those induced by M. humicola infection, including the chi tinase-like ‘ chil’ genes that promote defense against this pathogen (S10 Table).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably these genes do not include the well-characterized neuropeptide nlp defense genes, although they do include many of the pals genes. A more recently described natural pathogen of C. elegans is Myzocytiopsis humicola , which is an oomycete that also infects through the epidermis and causes a lethal infection [19]. Here as well, pals-22/25 regulate a significant number of genes in common with those induced by M. humicola infection, including the chi tinase-like ‘ chil’ genes that promote defense against this pathogen (S10 Table).…”
Section: Resultsmentioning
confidence: 99%
“…Here as well, pals-22/25 regulate a significant number of genes in common with those induced by M. humicola infection, including the chi tinase-like ‘ chil’ genes that promote defense against this pathogen (S10 Table). Interestingly, these chil genes, like the pals genes, are species-specific [8, 19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three antiviral responses are known of which RNA interference (RNAi) and uridylation both target viral RNA for degradation [7,[9][10][11]. The third response, the so-called Intracellular Pathogen Response (IPR), is thought to relieve proteotoxic stress from the infection by the OrV and other intracellular pathogens [12][13][14][15]. The 80 genes involved in the IPR pathway are controlled by pals-22 and pals-25 that function as a molecular switch between growth and antiviral defense.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression analysis in this model organism constitutes a powerful tool to discover new roles for different types of molecules. Traditionally, a set of housekeeping genes encoding actin (act-1) [7,8], tubulin (tba-1) [9][10][11], glyceraldehyde-3-phosphate dehydrogenase (gpd-2) [12,13], translation initiation factor 3C (eif-3.C) [14,15], calsequestrin (csq-1) [13,16], Rho GTPase (cdc-42) [17][18][19][20], and peroxisomal membrane protein related (pmp-3) [18,21] were thought to be appropriate reference genes for the normalization of gene expression in C. elegans. However, some reports indicated that the transcription levels of these conserved reference genes may be changed under different conditions, such as developmental stages, drug treatments, and hypoxia [22,23].…”
Section: Introductionmentioning
confidence: 99%